Gambaran Penggunaan Obat Pada Hepatitis A Pasien Rawat Inap di Rumah Sakit Umum Daerah dr. Soediran Mangun Sumarso Wonogiri Periode Januari 2017 – Juni 2019 - Noor Hidayati, Listiana; Dian Anggraini, Truly (Jurnal Farmasi (Journal of Pharmacy), 2020)
Hepatitis A is an infectious disease of the liver caused by the hepatitis A virus. Number of cases of hepatitis A inpatients at the Regional General Hospital dr. Soediran Mangun Sumarso Wonogiri during 2017 - June 2019 as many as 110 patients. The purpose of this study was to determine the description of drug use in hepatitis A patients including the characteristics and treatment of patients. This research is a non-experimental study with a descriptive analysis design, by collecting data information through medical records of hepatitis A patients diagnosed in the period January 2017 - June 2019. The parameters used are the percentage of the characteristics of hepatitis A patients calculated based on age, sex, type of comorbidities and description of treatment of hepatitis A patients including the type and amount of drug used, the type and amount of infusion fluid used. The results showed that the percentage based on the age of patients with the most age range ≥ 56 years (30.91%), the percentage based on the most sexes of men (55%), the percentage based on the types of comorbidities with most types of typhoid disease (53.33%) , the percentage based on the use of drugs that are widely used is curcuma (12.37%), and the percentage based on the use of most intravenous fluids is ringer acetate (58.78%).